2013
DOI: 10.5539/gjhs.v5n6p142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in Type 2 Diabetes Mellitus Using NCEP-ATPIII, IDF and WHO Definition and Its Agreement in Gwalior Chambal Region of Central India

Abstract: The aim of study was to determine the prevalence of metabolic syndrome (MetS) in people with type 2 diabetes mellitus (T2DM). National Cholesterol Education Program (NCEP) ATPIII Criteria, International Diabetes Federation and the World Health Organization (WHO) definitions were used in quantifying the metabolic syndrome and also the concordance between these three criteria’s used for identifying metabolic syndrome.Methods:This cross-sectional study involved 700 type 2 diabetic subjects from the urban areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
59
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 41 publications
17
59
4
2
Order By: Relevance
“…Also pending the availability of more specific data, the Europid waist circumference cutoff, which was implored in this study, has been advocated for the sub‐Sahara African population . The prevalence of MetS in the general population ranges between 17% and 25% . In our study, the frequency of MetS compared with that of a previous study by Ijeh and colleagues in Nigeria, who reported a prevalence rate of 30.7%, was at variant with the study by Ulasi and colleagues, who reported a lower prevalence of 15.9% in a Nigerian community.…”
Section: Discussionsupporting
confidence: 58%
“…Also pending the availability of more specific data, the Europid waist circumference cutoff, which was implored in this study, has been advocated for the sub‐Sahara African population . The prevalence of MetS in the general population ranges between 17% and 25% . In our study, the frequency of MetS compared with that of a previous study by Ijeh and colleagues in Nigeria, who reported a prevalence rate of 30.7%, was at variant with the study by Ulasi and colleagues, who reported a lower prevalence of 15.9% in a Nigerian community.…”
Section: Discussionsupporting
confidence: 58%
“…Recent evidence has described the prevalence of metabolic syndrome in Canada, 54 Latin America, 55 India, 56,57 Bangladesh, 58 Iran, 59 Nigeria, 60 South Africa, 61 and Vietnam, 62 as well as many other countries. On the basis of data from NIPPON DATA, the age-adjusted prevalence of metabolic syndrome in a Japanese population was 19.3%.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…It was not possible to achieve a comparable outcome definition of MetS across all studies, as different criteria (NCEP-ATP III or IDF) were used and two studies substituted BMI for waist circumference in their definition of abdominal obesity. However, the NCEP-ATP III and IDF definitions have been found to show good agreement in the diagnosis of MetS [42], [43]. Additionally, BMI has been suggested as equally effective as waist circumference for predicting the development of metabolic disorders[44], [45] and has been adopted in previous studies of the MetS [1], [46].…”
Section: Discussionmentioning
confidence: 99%